Case Study Analysis Of Successful Companies' Use Of Digital Twin To Reduce Waste - Yas Abbas; Ali Hameed; Ghufran mohammed (Harmoni Economics: International Journal of Economics and Accounting, 2025)
The purpose of this research is to build a review study to analyse the situation of successful companies in the use of digital twinning to reduce waste and losses that occur in the lack of accurate investment of time and efforts made, and from this basis was presented a set of previous studies related to digital twinning in order to determine the findings of these studies and discuss them by identifying points of similarity and difference between these studies,  And then come up with an idea and a new mechanism to determine the behaviours that companies can pursue in order to apply digital twinning, and on this basis the research discussed the conceptual framework of digital twinning and then the mechanisms through which companies can use it in order to develop their ability to achieve strategic success and competitiveness, the research has come out with several results, foremost of which was that digital twinning works to build a digital model that parallels competing companies through data analysis, improving their efficiency, accelerating innovation, predicting trends, and Then improve the customer experience and achieve integration between the current systems and the systems pursued by other companies.